2011
DOI: 10.1590/s0034-737x2011000500011
|View full text |Cite
|
Sign up to set email alerts
|

Uso de aminoetoxivinilglicina na maturação e queda pré-colheita de maçãs 'Imperial Gala'

Abstract: Aminoethoxyvinylglycine on maturation and preharvest drop control of 'Imperial Gala' applesThe use of techniques for controlling fruit maturation is critical in the production of 'Gala' apples in order to increase postharvest fruit preservation and reduce preharvest fruit drop. The objective of this work was to evaluate the effect of different concentrations, application times and multiple applications of aminoethoxyvinylglycine (AVG) on maturation and preharvest fruit drop of 'Imperial Gala' apples. The exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
1
5
1
Order By: Relevance
“…GA3 effects on fruit firmness has been associated to a reduction in approximately 10% of LP degree of cherry tomatoes (Ding et al, 2015), contrasting with what was here reported for cashew apples, and to inhibition of PG activity in 'Barhee' dates (Mohamed et al, 2014). Although in the current research there was no significant difference between control and AVG treatment regarding fruit firmness, previous studies have demonstrated a positive effect of AVG on firmness of peach, apple and persimmon (Hawerroth et al, 2011;Yildiz et al, 2012;Brackmann et al, 2013).…”
Section: Discussioncontrasting
confidence: 90%
“…GA3 effects on fruit firmness has been associated to a reduction in approximately 10% of LP degree of cherry tomatoes (Ding et al, 2015), contrasting with what was here reported for cashew apples, and to inhibition of PG activity in 'Barhee' dates (Mohamed et al, 2014). Although in the current research there was no significant difference between control and AVG treatment regarding fruit firmness, previous studies have demonstrated a positive effect of AVG on firmness of peach, apple and persimmon (Hawerroth et al, 2011;Yildiz et al, 2012;Brackmann et al, 2013).…”
Section: Discussioncontrasting
confidence: 90%
“…This technique is particularly important in the country, since approximately 95% of the apple production is concentrated in these two cultivars (PÉRÈS, 2009). Schedule of harvest prevents crop losses due to pre-harvest drop and / or post-harvest deterioration associated with the harvesting of overripe apples, and reduces harvesting costs (HAWERROTH et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that more than 95% of apples harvested are of only two cultivars, 'Gala' and 'Fuji' (PÉRÈS et al, 2009), the occurrence of unfavorable climatic conditions, particularly precipitation in the harvest time and insufficient availability of labor and infrastructure for harvesting, reception and handling at warehouse. The planting of apple trees in regions with different microclimates and the use of growth regulators to manage the dormancy release, flowering time and fruit maturation on the tree have been used to schedule the harvest time and to reduce the risk of harvesting immature and overripe apples (HAWERROTH et al, 2011;PETRI et al, 2011;SCOLARO et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The growth regulator aminoethoxyvinylglycine (AVG) is commercially sprayed on apple trees to increase the harvest period by delaying maturation through its inhibitory action on ethylene synthesis (Brackmann et al, 2014;Soethe et al, 2019). The application of AVG slows down the degradation of starch, as well as the loss of flesh firmness (Steffens et al, 2006), and can provide an increase in yield, due to a reduction in pre-harvest drop and an increase in average fruit mass (Hawerroth et al, 2011;Arseneault & Cline 2016). However, the pre-harvest application of AVG, at the recommended rate of 124 mg L -1 , reduces the development of the red skin color of 'Royal Gala' apples (Scolaro et al, 2015), damaging their visual aspect and depreciating the value of production.…”
Section: Introductionmentioning
confidence: 99%
“…The recommendation for AVG use is to apply it, in a single rate, four weeks before the start of harvest forecast (Yuan & Carbaugh, 2007). However, multiple applications of AVG can provide the same benefitsdelay of maturation -as the application of AVG in a single rate, but without compromising the development of the red color of the fruits (Hawerroth et al, 2011). For this reason, it is important to assess the effects of the multiple application of AVG, in combination or not with ethephon, to maintain the efficiency of AVG in regulating the ripening process, without, however, affecting the development of fruit skin color.…”
Section: Introductionmentioning
confidence: 99%